FERTILITY IMPROVEMENT THROUGH SYNCHRONIZATION OF OESTRUS IN COWS - IKHAR, A M; INGAWALE, M V; PAWSHE, C H; DESHMUKH, S G (The Indian Journal of Animal Reproduction, 2023)
The objective of the present research work was to study the efficacy of PGF2a for oestrus synchronization and GnRH on conception rate in synchronized cows under field condition. Totally 50 normal cyclic postpartum cows were selected from field condition and divided into five groups, containing ten experimental cows in each group. These groups were divided mainly as control group, hormonal treated group and non hormonal treated group. Out of thirty treated cows with PGF2a, twenty three (77.77%) and thirty (100 %) cows responded after first and 11 th day treatment .In Group-II 2 (20%) cows exhibited oestrus up to 30 days after pre synchronization treatment. The time required for onset of oestrus differs significantly in hormonal and non hormonal treated groups. Conception rate was higher in Group-IV than other groups which differ significantly in different groups.